THE ROLE OF ORGANIZATIONAL CULTURE AND PRINCIPAL LEADERSHIP IN ACHIEVING VISION AND MISSION oF SDN 1 GEBANGUDIK - Nafisa, Fida Sary (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2026)
Schools, as strategic educational institutions, require a positive organizational culture and effective leadership to support the achievement of educational goals. Previous studies have tended to examine the influence of organizational culture or leadership separately, while studies specifically examining the mechanisms of alignment between the two in the implementation of vision and mission in public elementary schools in non- urban areas are still limited. This study aims to examine the role of organizational culture and principal leadership in achieving the vision and mission at SD Negeri 1 Gebangudik, Cirebon Regency. The method used is descriptive qualitative, with data collection techniques through interviews, observation, and documentation of the principal and eight teachers. Data were analyzed through the stages of reduction, presentation, and drawing conclusions. The results show that a strong and positive organizational culture, characterized by the values of cooperation, openness, and effective communication, along with participatory and communicative principal leadership, form a mutually reinforcing relationship in creating a school climate conducive to the implementation of the vision and mission. This study contributes to the educational management literature by demonstrating that the alignment between participatory leadership and collaborative organizational culture is a key mechanism for implementing the school vision at the elementary level. The practical implications of this research emphasize the importance of synergistic management of organizational culture and principal leadership as a strategy to improve the quality of education in elementary schools.